RELATIONSHIP BETWEEN ENABLING PARENTING STYLE AND TEACHER CONSTRAINING WITH IDENTITY CRISIS RESOLUTION IN THE RELIGIOUS DOMAIN - Akmil Riza; Nuraini; Lahmuddin Lubis (RADJA PUBLIKA, 2023)
There is a problem of the failure of some students in resolving religious domain identity crises while in Islamic boarding schools because of the teacher's parenting style. Because this study aims to determine the relationship between enabling and constraining teacher parenting styles with the resolution of students' identity crisis in the religious domain. The research used an associative quantitative method with research subjects who were respondents to all of the Nurul Hakim Deli Serdang Modern Islamic Boarding School students who were classified as in the late adolescent phase. Using the parenting style scale to measure enabling and constraining variables, the exploratory scale and the commitment scale to measure identity crisis resolution variables. The hypothesis is associative with ordinal scale data. Meanwhile, to test the hypothesis using one of the analysis techniques of non-parametric statistical types, namely the Rank Spearman correlation test. There is a very strong relationship between teacher enabling parenting style and exploration in identity crisis resolution in the domain of religion. There is a very strong relationship between teacher enabling parenting style and commitment in identity crisis resolution in the religious domain. There is a weak relationship between teacher constraining parenting style and exploration in identity crisis resolution in the religious domain. There is a weak relationship between constraining teacher parenting style and commitment to resolution of identity crisis in the religious domain. There is a very strong relationship between teacher enabling parenting style and commitment in identity crisis resolution in the religious domain. There is a weak relationship between teacher constraining parenting style and exploration in identity crisis resolution in the religious domain. There is a weak relationship between constraining teacher parenting style and commitment to resolution of identity crisis in the religious domain. There is a very strong relationship between teacher enabling parenting style and commitment in identity crisis resolution in the religious domain. There is a weak relationship between teacher constraining parenting style and exploration in identity crisis resolution in the religious domain. There is a weak relationship between constraining teacher parenting style and commitment to resolution of identity crisis in the religious domain.